Care coordination, consistency and continuity: the case of the key worker role in children’s cancer care - Ana Martins; Susie Aldiss; Rachel M Taylor; Faith Gibson (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Purpose The overall aim was to evaluate the key worker role across principal treatment centres for children with cancer in England, Wales and Scotland. Methods Mixed-methods case study gathering data from multiple perspectives using questionnaires, interviews, focus groups and reports/performance documents over a two-year period. Framework approach was adopted to analyse transcripts and documentary data. Results Participants included: 22 nurse specialist key workers, 103 parents, 85 professionals and 10 children/young people. Qualitative and quantitative data were woven together, to best illuminate key worker services. Four main models of care were described as well as the context of care and process of care. Key working effectiveness centred around three pillars: care coordination; expert knowledge, experience and expertise; relationship. These were essential to improved family experience, emotional wellbeing, and delivery of individualized care closer to home. Conclusions The role is complex and diverse, responding to local needs. Certain conditions, (e.g., high caseload) placed limits on enacting the three pillars, diminishing the positive experience of families. When they worked well, key workers reduced the fragmented nature of services and families placed great value on keeping the same key worker from diagnosis into long-term care. Retaining these roles, where already in place, or including, if not, we would recommend, factoring into budgets to sustain and expand such roles.